2019
DOI: 10.1371/journal.pone.0215139
|View full text |Cite
|
Sign up to set email alerts
|

Molecular determinants of WNT9b responsiveness in nephron progenitor cells

Abstract: Primed nephron progenitor cells (NPCs) appear in metanephric mesenchyme by E11.5 and differentiate in response to the inductive WNT9b signal from the ureteric bud. However, the NPC WNT-receptor complex is unknown. We obtained M15 cells from E10.5 mesonephric mesenchyme and systematically analyzed components required for canonical WNT9b-responsiveness. When M15 cells were transfected with a β-catenin luciferase reporter plasmid, exposure to recombinant WNT9b resulted in minimal luciferase activity. We then anal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…It has been long-appreciated that a UB-derived Wnt9b canonical signal is required for both maintenance of self-renewal capacity of NPC, as well as for their differentiation 71 , 72 . Recently, work in cells derived from E10.5 mesonephric mesenchyme identified a role for Rspo1, Lrp6, and Fzd5 in enabling Wnt9b-responsiveness as cells transitioned from the intermediate mesoderm to the metanephric mesenchyme identity 73 . It was further demonstrated that low signaling input promotes self-renewal and high signaling input promotes differentiation 74 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been long-appreciated that a UB-derived Wnt9b canonical signal is required for both maintenance of self-renewal capacity of NPC, as well as for their differentiation 71 , 72 . Recently, work in cells derived from E10.5 mesonephric mesenchyme identified a role for Rspo1, Lrp6, and Fzd5 in enabling Wnt9b-responsiveness as cells transitioned from the intermediate mesoderm to the metanephric mesenchyme identity 73 . It was further demonstrated that low signaling input promotes self-renewal and high signaling input promotes differentiation 74 .…”
Section: Discussionmentioning
confidence: 99%
“…26 Thus, we hypothesized that the morphological changes observed in the stromal Tcf21 KO kidney are mediated by disruption in β-catenin signaling. Using the metanephric mesenchyme mouse cell-lines MK3 and M15 27,28 we examined the effect of Tcf21 on Wnt/ β-catenin signaling. Immunostaining for β-catenin in Foxd1CreTcf21 f/f kidneys showed markedly reduced expression in the medullary stroma at E14.5 and E16.5 (Figure 5A, A', B, B').…”
Section: Tcf21 Cooperates With β-Catenin To Promote Wnt Signaling In ...mentioning
confidence: 99%
“…How is nephrogenesis then restricted to the branch corner region? Given the complexity of canonical WNT signaling with its many redundant pathway components [29, 39, 49] and the extensive cross-talk of the WNT9b/WNT4/SIX2 core network with other signalling pathways [3, 12], pre-existing differences in WNT responsiveness could, in principle, spatially restrict PTA/RV formation. Also, BMP7 signalling via the mitogen-activated protein kinase (MAPK) pathway maintains progenitors, while SMAD-mediated BMP7 signalling primes progenitors for WNT/ β -catenin mediated differentiation [2, 3].…”
Section: Introductionmentioning
confidence: 99%